Dual pH-/thermo-responsive chitosan-based hydrogels prepared using "click" chemistry for colon-targeted drug delivery applications. (15th May 2021) - Hoang, Huong Thi; Jo, Sung-Han; Phan, Quoc-Thang; Park, Hansol; Park, Sang-Hyug; Oh, Chul-Woong; Lim, Kwon Taek
Graphical abstract: Highlights: pH-/thermo-responsive hydrogels were prepared using PAA, CsNb, and bisTz-PNIPAM. Porous structure formed by Tz-Nb reaction greatly increased the drug loading content. Hydrogels released a much higher amount of drug at pH 7.4 than at pH 2.2. The drug release from hydrogels was enhanced at 37 °C via "shrinkage" of PNIPAM. Abstract: A dual pH-/thermo-responsive hydrogel was designed based on a polyelectrolyte complex of polyacrylic acid (PAA) and norbornene-functionalized chitosan (CsNb), which was synergized with chemical crosslinking using bistetrazine-poly(N-isopropyl acrylamide) (bisTz-PNIPAM). The thermo-responsive polymeric crosslinker, bisTz-PNIPAM, was synthesized via reversible addition–fragmentation transfer polymerization of NIPAM. FTIR, XRD, rheological and morphological analyses demonstrated the successful formation of the polyelectrolyte network. The highly porous structure generated through the in-situ "click" reaction between Tz and Nb resulted in a higher drug loading (29.35 %). The hydrogel (COOH/NH2 mole ratio of 3:1) exhibited limited drug release (8.5 %) of 5-ASA at a pH of 2.2, but it provided an almost complete release (92 %) at pH 7.4 and 37 °C within 48 h due to the pH responsiveness of PAA, hydrogel porosity, and shrinkage behavior of PNIPAM. The hydrogels were biodegradable and non-toxic against human fibroblast cells, suggesting their considerable potential for a colon-targeted drug delivery system.